Pharmacological Disruption of Phosphorylated Eukaryotic Initiation Factor-2α/Activating Transcription Factor 4/Indian Hedgehog Protects Intervertebral Disc Degeneration via Reducing the Reactive Oxygen Species and Apoptosis of Nucleus Pulposus Cells - Bao, Junping; Qian, Zhanyang; Liu, Lei; Hong, Xin; Che, Hui; Wu, Xiaotao (Frontiers in Cell and Developmental Biology, 2021)
Excessive reactive oxygen species (ROS) and apoptosis in nucleus pulposus (NP) cells accelerate the process of intervertebral disc degeneration (IDD). Here, we used an integrated into pathological samples, in vitro, and in vivo framework to investigate the impact of phosphorylation of eukaryotic initiation factor-2α (p-eIF2α)/activating transcription factor 4 (ATF4)/Indian hedgehog (Ihh) signalling in the IDD. From the specimen analysis of the IDD patients, we found the p-eIF2α, ATF4 and Ihh protein levels were positively related while the NP tissue went degenerative. In vitro, TNF-α caused the NP cells degeneration and induced a cascade upregulation of the p-eIF2α, ATF4, and Ihh. Interestingly, ATF4 could activate Ihh through binding its promoter region, and silencing of ATF4 decreased Ihh and protected the NP cells degeneration. Moreover, ISRIB inhibited the p-eIF2α, resulted in a suppression of ATF4/Ihh, and alleviated the TNF-α induced ROS production and apoptosis of NP cells. On the contrary, further activating p-eIF2α aggravated the NP cells degeneration, with amplification of ATF4/Ihh and a higher level of ROS and apoptosis. Additionally, applying cyclopamine to suppress Ihh was efficient to prevent NP cells apoptosis but did not decrease the ROS level. In vivo of a mouse instability-induced IDD model, ISRIB suppressed p-eIF2α/ATF4/Ihh and prevented IDD via protecting the anti-oxidative enzymes and decreased the NP cell apoptosis. Cyclopamine prevented NP cells apoptosis but did not affect anti-oxidative enzymes expression. Taken together, p-eIF2α/ATF4/Ihh signalling involves the ROS level and apoptosis in NP cells, and pharmacological disrupting of which may provide promising methods in preventing IDD.